Demographic dividend, digital innovation, and economic growth: Bangladesh experience - Kazi Arif Uz Zaman; Tapan Sarker (Asian Development Bank Institute (ADBI), 2021)
This study aims to understand the linkages between demographic dividends, digital innovation, and economic growth, using Bangladesh as a case study. It adopts a three-stage least squares (3SLS) model to explore how and to what extent the digitization and demographic transition lead towards faster economic growth in Bangladesh. Results imply that economic growth is significantly influenced both by digitization and the demographic transition. Estimation reveals that with an increase of 1 percentage point in the number of internet users, the GDP would increase by 0.11%, ceteris paribus, while a 10-basis point decrease in the dependency ratio would increase the GDP by 7.2%, on average. The key driving factors for digitization are the labor participation rate, workers' productivity, and mobile penetration. The urbanization rate, however, adversely impacts the rise in internet users. Estimations imply that the Human Development Index (HDI) score and urbanization rate have significant negative impacts on the dependency ratio, while female participation in the labor force has a positive impact on it. The study provides insights to assist the government and policymakers in framing a roadmap on how Bangladesh could utilize demographic transition to achieve faster economic growth while fostering digitization and technological innovation. Lessons learned could also be used in other developing countries in the Asia and Pacific region.
Keywords: J11; J24; L81; L86; O32; 330; demographic dividend; digital innovation; e-commerce; economic growth; Bangladesh